Equitable access: Remote and rural communities 'transport needs' - Peter White (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2011)
Transport in rural and remote regions receives considerable attention in research, but this is often focussed on specific means of resolving problems in those regions - for example, the role of demand-responsive bus services, or scope for attracting users to rail services. The aim of this paper is to take a broader view, firstly in defining what constitute rural and remote regions, and secondly in considering a wide range of public transport options available. Experience in Britain will be taken as a starting point, since extensive research has been conducted here, and rural issues are also a focus of much public debate at present. Findings from other European countries will also be examined.
Keywords: 330